2016
DOI: 10.1098/rspa.2015.0453
|View full text |Cite
|
Sign up to set email alerts
|

One hundred years of complex dynamics

Abstract: Holomorphic dynamics has been a key area of study for 100 years. In this survey, we focus on the dynamics of rational functions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 128 publications
0
8
0
1
Order By: Relevance
“…A map f a is structurally stable if f c is topologically conjugate to f a , for every c in an open set containing a. For rational maps on the Riemann sphere J-stability, which roughly speaking means stability on a neighborhood of the Julia set, is usually considered [4]. Mañé, Sad and Sullivan [7] have shown that the set of J-structurally stable rational maps is open and dense in the space of rational maps Rat d of the same degree.…”
Section: Dynamics Of Quadratic Mapsmentioning
confidence: 99%
See 4 more Smart Citations
“…A map f a is structurally stable if f c is topologically conjugate to f a , for every c in an open set containing a. For rational maps on the Riemann sphere J-stability, which roughly speaking means stability on a neighborhood of the Julia set, is usually considered [4]. Mañé, Sad and Sullivan [7] have shown that the set of J-structurally stable rational maps is open and dense in the space of rational maps Rat d of the same degree.…”
Section: Dynamics Of Quadratic Mapsmentioning
confidence: 99%
“…In 1994 the first author and C. Penrose proved that for all parameters a in the real interval [4,7], the correspondence F a is a mating between a quadratic polynomial f c (z) = z 2 + c, c ∈ [−2, +1/4] ⊂ R and the modular group Γ = P SL(2, Z) (see [1]).…”
Section: This Is a Version Of Minkowski's Question Mark Functionmentioning
confidence: 99%
See 3 more Smart Citations